Intraperitoneal Hydrocortisone plus Bupivacaine versus Bupivacaine alone for Pain Relief after Laparoscopic Cholecystectomy: A Randomized Controlled Trial - Sharma, Mahesh; Kharbuja, Kalpana; Sharma, Nil Raj (Journal of Lumbini Medical College, 2016)
Introduction: Laparoscopic cholecystectomy has been the gold standard in the treatment of gallstones since last decades. Beside several benefits of laparoscopic cholecystectomy compared with open surgery, postoperative pain is still a frequent melancholy. Hence, pain management is utmost regarding patients' comfort. The main objective of the study was to compare the effect of intraperitoneal hydrocortisone plus bupivacaine with bupivacaine alone on pain relief following laparoscopic cholecystectomy. Methods: A randomized study was conducted from December 2015 to August 2015 that included 100 patients aged 20 to 60 years of both genders who were found to have symptomatic gallstones and were scheduled for elective laparoscopic cholecystectomy at Lumbini Medical College. Patients randomly received 100 mg hydrocortisone plus 100 mg bupivacaine in 200 ml normal saline (group A) or 100 mg bupivacaine in 200 ml normal saline (group B) into the peritoneum. Post-operative abdominal and shoulder pain were evaluated using Visual Analog Score (VAS). The patients were also followed up for postoperative analgesic requirements, and recovery variables. Data were collected, tabulated and analyzed statistically using SPSS version 19. Results: Total number of patients in this study were 100. Age and gender among both groups were comparable. VAS scores for pain was significantly lower for group A as compared to group B at 0, 2, 4, 6, 12, and 24 hours. Time of oral intake in hrs for liquids and solids was statistically significant in Group A compared to Group B. Rescue analgesic requirement was also significantly low in Group A compared to Group B. Hospital stay in both group were comparable. Conclusion: Combination of hydrocortisone plus bupivacaine can relieve pain after laparoscopic cholecystectomy better compared to bupivacaine alone when administered intraperitoneally. DOI: https://doi.org/10.22502/jlmc.v3i2.71 J. Lumbini. Med. Coll. Vol 3, No 2, July-Dec 2015. Page: 41-44